Production Planning and Control as Routing in Manufacturing Networks - Bach, Terje; Jæger, Bjørn; Hoff, Arild (Institute of Automation and Computer Science, Brno University of Technology, 2018)
In this paper, we explore the use of network routing for production planning and control in manufacturing of complex industrial products. Such a product is the result of a joint effort of many manufacturing companies; each considered a collection of work centre nodes connected by transportation links forming a company-wide manufacturing network. Each company is, in turn considered a manufacturing node connected to other manufacturers by transportation links forming a distributed manufacturing network that produces the final product. We model the manufacturing network as a distribution network where the incoming and outgoing inventories of products are distinct nodes in addition to the work centre nodes. Production planning and control are done by minimizing the cost of handling all products in all work centre nodes. This formulation provides a scalable and flexible production planning and control scheme adhering to the networked structure of manufacturing of complex products. We apply the model to a company-wide manufacturing network as a first approach. A case study using the model demonstrates production planning using network routing at a manufacturer of ship propulsion engines.
Keywords: Discrete manufacturing; next generation manufacturing systems; industry 4.0; advanced manufacturing; smart manufacturing